The impact of the rural infrastructure support programme on poverty alleviation projects at Greater Giyani Municipality, Mopani District, Limpopo Province - Nkanyani, Basambilu Eunice (My University, 2017)
Rural areas of South Africa are characterised by high levels of unemployment and poverty resulting from lack of economic infrastructure. This led to the initiation of the Comprehensive Rural Development (CRDP) in 2009 to address poverty and lack of development in rural areas. Infrastructure provision to rural communities was identified as one of the main priorities of government. It was piloted in Muyexe village of Limpopo Province due to its lack of basic infrastructural services. This study was undertaken to investigate the impact made to cooperatives through the utilization of the infrastructures in terms of income generation and poverty alleviation. It also aimed at determining how sustainable the programme will be in the long-term. The key research questions asked were to determine if infrastructure provision could contribute to poverty alleviation and to determine how sustainable such programmes may be. Again, the study had to evaluate how the programme was implemented, to identify challenges faced and the gaps. It also recommends the solutions for future implementation of the programme. The study used a quantitative survey questionnaire which was administered to 30 beneficiaries of the projects. The findings of the study revealed that infrastructure for farming, brick laying, arts and craft and cosmetics manufacturing were provided to the cooperatives depending on their needs. The infrastructure provision programme contributed to improving the working conditions of the cooperatives but the impact made in terms of job creation, income generation, improving livelihoods and poverty alleviation is limited to a number of households. The programme had loopholes during its implementation due to lack of integration between the spheres of government and also lack of proper consultation. Cooperatives are still faced with a high challenge of lack of infrastructure because the infrastructure supplied was insufficient. The study recommends that proper consultation must be done to ensure that there is maximum participation by all concerned stake holders including the community. Effective mechanisms for training, supervision and designing of monitoring tools must also be done. Due to time, a larger sample could not be done and future research needs to be undertaken on a lager sample and also on the management of infrastructure provided to ensure that there is accountability amongst cooperatives.
Thesis (M. Dev.) -- University of Limpopo, 2017
Keywords: Unemployment and Poverty; Rural development; Rural communities; Cooperatives; Agricultural development projects; Poverty - South Africa - Limpopo Province